2015
DOI: 10.1080/21690731.2015.1112458
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a class of standardized and interchangeable parts utilizing programmed ribosomal frameshifts for synthetic biology applications

Abstract: Synthetic biology and the rational design of biological devices depend on the availability of standardized and interchangeable biological parts with diverse range of functions. Reliable access to different reading frames during translation has largely been overlooked as functionality for bioengineering applications. Here we report the construction and initial characterization of the first member of such a class of biological parts that conforms to the BioBrick Standard (RFC25), allowing its interchangeable use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The tRNAs we have identified are relatively efficient at missense suppression and these tRNAs will continue to be useful tools for genetic analyses and synthetic biology applications (e.g. ( 75 )). The spontaneous nature of the selection process and the limited consequences of the genetic code change on growth suggest that tRNA alleles resulting in mis-aminoacylation may become fixed in a population where they confer advantage and may be more common than previously assumed.…”
Section: Discussionmentioning
confidence: 99%
“…The tRNAs we have identified are relatively efficient at missense suppression and these tRNAs will continue to be useful tools for genetic analyses and synthetic biology applications (e.g. ( 75 )). The spontaneous nature of the selection process and the limited consequences of the genetic code change on growth suggest that tRNA alleles resulting in mis-aminoacylation may become fixed in a population where they confer advantage and may be more common than previously assumed.…”
Section: Discussionmentioning
confidence: 99%
“…There have been two recent studies pertinent to synthetic biology ( 699 , 700 ). One generated synthetic ligand-responsive stimulators for eukaryotic −1 frameshifting at U_UUA_AAC.…”
Section: Stimulators Overviewmentioning
confidence: 99%
“…Interestingly, we found that INPP4B significantly promoted the expression of cyclinD1 protein, but had little effect on the RNA expression levels of CCND1. These results may be attributed to the fact that CCND1 contains relatively long and structured 5′-untranslated regions, which makes it more dependent on the unwinding activity of eIF4A within the eIF4F complex, and thus highly sensitive to the levels of eIF4E in the cell 22. Since both INPP4B and phosphorylated 4E-BP1 have been reported to be overexpressed in CRC tissues, and it was found that INPP4B enhanced 4E-BP1 phosphorylation in CRC cells, it is interesting to explore the correlation between INPP4B and phosphorylated 4E-BP1 expression in clinical tissues.…”
Section: Discussionmentioning
confidence: 99%